The Arab spring: its origins, evolution and consequences… four years on - Abdel Salam, El Fatih Abdullahi (IIUM Press, 2015)
The Middle East and North Africa (MENA) has long been laden with tension and instability. However, the recent Arab Uprisings, better known as the Arab Spring, have intensified volatility, turning this “hot-spot” into a veritable tinderbox whose potential for explosion has far-reaching national, regional and global implications. This review analyses and describes the events leading to the Arab Spring. It also looks at the impacts and ramifications of the upheavals on the national, regional and international levels. The review argues that the Arab Spring has both changed and charged some of the region’s thorniest problems- from the rise of political Islam to civil wars to rivalries between key regional powers. It raises important questions concerning the impact of the Arab Spring: were these uprisings a deceptive and transient phase of popular anger, or were they a genuine harbinger leading to genuine democratic transition? The review focuses also on the online networking and digital technologies as effective methods of aggregate activism to by-pass state owned media. Finally, the review offers an assessment of whether the MENA is destined for a political impasse or that political wisdom and prudence will prevail and save the region from the brink.